Pengaruh Inherent Risk dan Detection Risk Terhadap Kualitas Opini Audit - Kirana Ikhtiari; Ummu Kalsum; Syamsuri Rahim; Rina Anjarsari (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2021)
The opinion given by the auditor has an important impact on reporting the company's performance through the financial statements presented by the company's management. Through this role, the auditor's work is followed by several risk factors. This study empirically examines the effect of Inherent Risk, Control Risk, and Detection Risk on audit opinion quality. The population of this research is the auditors who work at the Public Accounting Firm in Makassar. The classical assumption test uses the normality test, heteroscedasticity test, and multicollinearity test. The hypothesis test used is multiple regression analysis with the help of SPSS software. This study indicates that inherent risk, control risk, and detection risk have a positive and significant effect on the quality of audit opinion.